Kejadian Putus Pakai (drop out) Kontrasepsi di Sumatera Utara Tahun 2017 - Riance Maria Sinaga (Inovasi, 2020)
Case when a contraceptive acceptors stop being acceptors is called a discontinued use case or also called Drop Out. Discontinuation rates indicates a problem with contraceptive use. This study aims to provide description about contraceptive dropouts in North Sumatra at 2017 based on data Program Performance Indicator KKBPK RPJMN Survey 2017. The study that was conducted is descriptive. The population referred to in this study were women of childbearring age 15-49 years who were respondents in Program Performance Indicator KKBPK RPJMN Survey 2017. Samples were women of childbearring age 15-49 years who had used contraceptive methods in the last 12 months but did not use tools / methods contraception when the survey was conducted. Data had been weighted and normalized before analyzed. The proportion of contraceptive discontinuation events in Sumatera Utara for women of childbearring age 15-49 years according to the RPJMN Indicator Survey data is as much as 7.4% or as many as 65 of 876 people who had used contraceptive methods in the last 12 months but have stopped when survey conducted. This study shows that the largest proportion of discontinuation events is in the age group of 35-39 years (40.2%), elementery and junior high school education (each has 31.0%), not working (58.6%), living in urban areas (56,0%) ), and medium wealth quintiles (38.4%). Based on contraceptive methods, the highest proportion of contraceptive discontinuation was in the 1-month injection contraception method (46.4%), followed by pill (30.1%)and the 3-month injection method (10.3%). Based on the number of children, the highest proportion of discontinuations in contraception was in respondents who had 3 children (49.6%). The biggest reason for dropping out were affraid of side effects (26.6%) and wanting to get pregnant (20,8%) on the second rank. It is expected that the implementation of better communication, information and education related to limiting the number of children, and group of women of childbearring in the age 30-34 years and 35-39 years which is the highest age group with the event of discontinuation can be the target of programme.